{Milder degenerative effects of Carfilzomib vs. Bortezomib in the Drosophila model: A link to clinical adverse events} - Tsakiri, Eleni N.; Terpos, Evangelos; Papanagnou, Eleni Dimitra; Kastritis, Efstathios; Brieudes, Vincent; Halabalaki, Maria; Bagratuni, Tina; Florea, Bogdan I.; Overkleeft, Herman S.; Scorrano, Luca; Skaltsounis, Alexios Leandros; Dimopoulos, Meletios A; et al. (Scientific Reports, 2017)
Proteasome inhibitors, e.g. Bortezomib (BTZ) and Carfilzomib (CFZ), have demonstrated clinical efficacy against haematological cancers. Interestingly, several adverse effects are less common, compared to BTZ, in patients treated with CFZ. As the molecular details of these observations remain not well understood we assayed the pathophysiological effects of CFZ vs. BTZ in the Drosophila experimental model. Mass Spectrometry analyses showed that neither CFZ nor BTZ are hydrolysed in flies' tissues, while at doses inducing similar inhibition of the rate limiting for protein breakdown chymotrypsin-like (CT-L) proteasomal activity, CFZ treatment resulted in less intense increase of oxidative stress or activation of antioxidant and proteostatic modules. Also, despite comparable cardiotoxicity likely due to disrupted mitochondrial function, CFZ did not affect developmental processes, showed minimal neuromuscular defects and reduced to a lesser extent flies' healthspan. Studies in flies, human cancer cell lines and blood cells isolated from Multiple Myeloma patients treated with CFZ or BTZ revealed, that the increased BTZ toxicity likely relates to partial co-inhibition of the caspase-like (C-L) proteasomal activity Supportively, co-treating flies with CFZ and a C-L selective proteasome inhibitor exacerbated CFZ-mediated toxicity. Our findings provide a reasonable explanation for the differential adverse effects of CFZ and BTZ in the clinic.